Subsidence prediction and mine design for underground coal mining in the Collie Basin - Misich, Ian J. (Curtin University, 1997)
The subsidence characteristics of the Collie Basin sediments have been investigated to provide site specific design criteria for the Wongawilli method of coal extraction. As historical coal extraction (bord and pillar) methods did not generally give rise to large scale subsidence, there were very few details on mining subsidence in the Collie Basin available to base any design methodology on. Consequently, the investigation was conducted on a Green fields basis. Firstly, the mechanisms involved in the development of mining subsidence needed to be investigated and identified. It was then necessary to determine the effects that mining subsidence would have on mine and ground mass (specifically aquitards) structures and surface features. Once these two areas of work were completed, design criteria were formulated to manage the effects of mining subsidence by controlling the critical mechanisms of subsidence development.The results from this study have greatly enhanced the level of understanding of the subsidence mechanisms involved, and allowed for the development of predictive models which can be used for the design of coal extraction by the panel/pillar mining method in the Collie Basin. Mine planning engineers can now use this design information to derive the most cost effective methods for the extraction of coal within the Collie Basin.